Magnesium isotope fractionation during hydrothermal seawater-basalt interaction. (1st March 2020) - Voigt, Martin; Pearce, Christopher R.; Fries, David M.; Baldermann, Andre; Oelkers, Eric H.
Abstract: Fluid-rock interactions in hydrothermal systems at or near mid-oceanic ridges (MOR) play a major role in determining the composition of the oceanic crust and seawater. To quantify the processes that govern cation exchange in these environments we have experimentally studied the isotopic evolution of δ 26/24 Mg in the fluid phase during seawater-basalt interaction at 250 and 290 °C. Mass balance constraints indicate that isotopically heavy Mg was preferentially incorporated into non-exchangeable (octahedral) sites in secondary clay minerals such as saponite (Mg-rich smectite), leaving residual fluids enriched in light Mg isotopes. The magnitude of fractionation observed during smectite precipitation in our experiments ( ε Smectite - Liquid 26 / 24 ) ranged from 0.35 ‰ to 0.42 ‰ . This observation, which contrasts with the preferential uptake of light Mg isotopes into biogenic and inorganic marine carbonates, highlights the potential utility of Mg isotopes as tracers of the precipitation dynamics of authigenic Mg-silicate and Mg-carbonate phases. Furthermore, although Mg isotopic fractionation is often masked by the almost complete removal of Mg in high temperature marine hydrothermal systems, our experiments demonstrate that it does become significant at lower temperatures where Mg removal by clay formation is incomplete. Under such conditions, this fractionation will create isotopically light fluids due to smectite precipitation, thus potentially represents an important component of the marine Mg isotope inventory.